2019
DOI: 10.1186/s12885-019-5466-y
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic and clinicopathological significance of PD-L1 expression in patients with diffuse large B-cell lymphoma: a meta-analysis

Abstract: Background Programmed cell death receptor 1 ligand 1 (PD-L1) expression in various tumors, including hematologic malignancies, has recently become a research topic of great interest. We performed a meta-analysis to evaluate the prognostic and clinicopathological value of PD-L1 expressed in tumor cells of patients with diffuse large B-cell lymphoma (DLBCL). Methods Relevant studies were identified from PubMed, EMBASE, Web of Science and the Cochrane Library. The hazard r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…Exosomal microRNAs (miRNAs), which are transferred by EVs, are promising and reliable tools for cancer diagnosis and clinical application [18]. PD-L1 overexpression has been examined as a prognostic factor in diverse cancers including lung cancer [19], gastric cancer [20], ovarian cancer [21], breast cancer [22], prostate cancer [23], bladder cancer [24], cervical cancer [25], cholangiocarcinoma [26], colorectal cancer [27], nasopharyngeal carcinoma [28], diffuse large B-cell lymphoma [29], pancreatic cancer [30], soft-tissue sarcoma [31], renal cell carcinoma [32], and head and neck squamous cell carcinoma [33]. In addition, in patients with melanoma, exosomal PD-L1 is an indicator of immune activation early after the initiation of treatment with immune checkpoint inhibitors (ICIs) and is associated with clinical response to ICIs [34].…”
Section: Introductionmentioning
confidence: 99%
“…Exosomal microRNAs (miRNAs), which are transferred by EVs, are promising and reliable tools for cancer diagnosis and clinical application [18]. PD-L1 overexpression has been examined as a prognostic factor in diverse cancers including lung cancer [19], gastric cancer [20], ovarian cancer [21], breast cancer [22], prostate cancer [23], bladder cancer [24], cervical cancer [25], cholangiocarcinoma [26], colorectal cancer [27], nasopharyngeal carcinoma [28], diffuse large B-cell lymphoma [29], pancreatic cancer [30], soft-tissue sarcoma [31], renal cell carcinoma [32], and head and neck squamous cell carcinoma [33]. In addition, in patients with melanoma, exosomal PD-L1 is an indicator of immune activation early after the initiation of treatment with immune checkpoint inhibitors (ICIs) and is associated with clinical response to ICIs [34].…”
Section: Introductionmentioning
confidence: 99%
“…Godfrey J et al study has demonstrated that DLBCL with PD-L1 gene alterations showed high risk features [3]. Meta-analysis also showed that PD-L1 expression was associated with poor OS and adverse clinicopathologic features in DLBCL [12].…”
Section: Discussionmentioning
confidence: 96%
“…Godfrey J et al study has demonstrated that DLBCL with PD-L1 gene alterations showed high risk features [3]. Meta-analysis also showed that PD-L1 expression was associated with poor OS and adverse clinicopathologic features in DLBCL [11]. In Y Wang et al study, as compared with those who have no gain of 9p24.1, DLBCL with 9p24.1 gain or amplification didn't show any significant survival separation [5].…”
Section: Discussionmentioning
confidence: 97%